The art of controlled destruction: reflections on archival appraisal and memory - Cougo Junior, Francisco Alcides (2019)
Introduction: The article questions the relations between archives and memory starting from archival functions of document evaluation. Objective: To use contemporary memory studies to reflect on the act of evaluating documents and their respective assessment of "values" for permanent custody. Methodology: bibliographic analysis and systematization of concepts of "sociotransmitters", forgetfulness, multidirectional memory and memorial governance. Results: the paper proposes an extention of the relations between memory, heritage and archives, overcoming the idea of archive just as a “place of memory” to accommodate the archival functions, its concepts, terms and theories. Conclusions: the concepts of "multidirectional memory", "memorial governance", and the document evaluation activity are approximated.